2010
DOI: 10.2134/jeq2008.0530
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Odorants in Swine Manure by Carbohydrate and Bacterial Amendments

Abstract: Malodors from pig manure storage pits are a problem lacking a cost-efficient solution particularly for small pig (Sus domestica) farms. The objective of this study was to reduce emissions of noxious odorants by changing the conditions in the pig manure to favor an altered microbial community. Sugars (maltose, lactose, and saccharose), carbohydrate-rich waste (maltose syrup and wheat flour), and bacterial amendments (Lactobacillus plantarum and L. amylophilus) were tested for their effect on manure pH, bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Inclusion of dietary fibre also can lead to a shift in N excretion from manure, which means from easy degradable urine urea to a more stable form of N in faecal microbial protein. This shift in N excretion can result in reduced ammonia emissions and therefore less environmental pollution , …”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of dietary fibre also can lead to a shift in N excretion from manure, which means from easy degradable urine urea to a more stable form of N in faecal microbial protein. This shift in N excretion can result in reduced ammonia emissions and therefore less environmental pollution , …”
Section: Introductionmentioning
confidence: 99%
“…Further, promoting microbially mediated self‐acidification of animal slurry via the addition of organic substances is not well explored. Although the benefits of adding organic substances have been demonstrated for ammonia emission and odor control in slurry (Clemens et al, 2002; Nykanen et al, 2010), their effect on CH 4 emissions has not been reported.…”
mentioning
confidence: 99%
“…In order to reduce NH3 emissions, biological additives seek to promote the metabolism of N in combination with the decomposition of OM, and then to stabilise N as organic N compounds within biomass in slurry, rather than remaining as NH3 to be volatilised (Wheeler et al, 2011). To control odour emission, a number of biological additives have been developed that seek to reduce the production, or to increase the degradation, of odorous volatile compounds (Nykänen et al, 2010). It has been observed that odorous compounds are produced under anaerobic conditions within slurry, mainly by Clostridium and Eubacterium spp.…”
Section: The Role Of Slurry and Slurry Additives In Agricultural Productionmentioning
confidence: 99%
“…that favour high pH (Zhu, 2000). Therefore, lowering slurry pH and adjusting the conditions during slurry storage to favour lactic acid bacteria should avoid conditions under which anaerobic bacteria release odorous compounds (Nykänen et al, 2010). Further, the use of aeration to influence the bacterial community in slurry, mainly composed of Bacillus spp.…”
Section: The Role Of Slurry and Slurry Additives In Agricultural Productionmentioning
confidence: 99%